Myelodysplasien: molekularer Hintergrund und klinische Implikationen = Myelodysplastic syndromes : molecular background and clinical implications - Müller, Nadine Zoé; Hofmann, Wolf-Karsten; Nolte, Florian (Der Onkologe, 2012)
Myelodysplastic syndromes (MDS) are hematopoetic disorders mainly of elderly patients. Although allogeneic stem cell transplantation is the only curative therapy in MDS. However, due to age and frequently coexisting morbidities only a minority is eligible for this approach. The demethylating agent 5-azacitidine is a highly effective drug, which has been approved for MDS patients with an increased medullary blast count. In low-risk MDS patients with isolated deletion 5q lenalidomide has demonstrated its high efficacy. However, it has not yet been approved in Germany in this indication. Most patients will depend on regular transfusions of packed red blood cells with the risk of development of iron overload. Recently, new high throughput technologies have identified various molecular alterations in patients with MDS and other myeloid malignancies. Some of them might be included in upcoming classification systems, while others might be of use in optimizing risk stratification scores. Identification of molecular defects might result in the advent of specific and targeted drugs leading to a more effective treatment in MDS in the future.
Gesehen am 13.04.2018